An opportunity model of safety risks among jail officers. (January 2020) - Ellison, Jared M.; Gainey, Randy
Abstract: Purpose: Correctional officers experience victimization and other safety hazards that may result in adverse health and occupational outcomes. Researchers have done their part to investigate the sources of safety risks for prison officers, but much less information has been gathered regarding the parallel dangers that jail officers endure. We drew from a general opportunity perspective to identify the correlates of safety risks among jail officers. Method: Using data collected from 1264 individuals working in 18 jails in two states, we examined whether measures of officers' routines, suitability as targets, and levels of guardianship influenced how often they were threatened, their risk of assault victimization, or their perceptions of danger at work. Conclusions: In general, our results showed that jail officers' safety risks vary according to their work assignments, degree of contact with inmates, antagonistic attitudes or characteristics, and extent of protection and support at work. Findings comport with the broader literature on safety and victimization as well as the small but growing number of studies that suggest individual and work-related conditions are important for identifying jail officers' safety risks. Highlights: Some work-related routines were especially dangerous for jail officers and those who were more antagonistic to inmates or experienced more challenging work conditions were victimized more often and felt their jobs were more dangerous. Perceptions of inadequate staffing were tied to greater safety risks and the level of officer victimization was greater in overcrowded jails. Findings offer potential avenues for new research and correctional policy aimed at preserving the health and safety of jail officers.